AB0029 Imbalance between Immunoregulatory and Effector TH17 Pathway in Active Sle. (10th June 2014) - Jakiela, B.; Kleczynska, W.; Kosalka, J.; Plutecka, H.; Sanak, M.; Musial, J.
Abstract : Background: Defective function of regulatory T cells (Treg) leads to the impairment of immune tolerance implicated in the pathogenesis of autoimmune inflammation in systemic lupus erythematosus (SLE). Methods: To investigate the role of Treg in SLE we studied peripheral blood Treg and CD4+ effector T-helper cells (Th1, Th17), expression of their signature cytokines by in vitro activated lymphocytes (real-time PCR), and levels of TGF-β1, IL-10 and IL-17A (ELISA) in sera from patients with active–SLE (n=13), inactive-SLE (n=13) and matched healthy subjects (n=13). Results: There was a significant decrease in CD4+ lymphocyte count in active SLE, with no evident difference in the percentage of CD25+FoxP3+ Treg cells as compared to other groups. Treg absolute counts decreased significantly in active-SLE (∼2-fold as compared to controls) and weakly correlated with markers of disease activity (C4, r=0.44). Only Th1 (IFN-γ producing) cells, but not Th17 (IL-17A producing) cells decreased in active disease, resulting in lower Th1/Th17 ratio. This was confirmed by a lower expression of IFN-γ mRNA (but not IL-17A) in peripheral blood lymphocytes from patients with active-SLE. All patients with SLE were characterized by lower Treg/Th17 ratio (median 1.4 vs. 2.4 in controls, p<0.001). Additionally, in patients with SLE exacerbation we observed higher levels of serum IL-17A (p<0.05 vs. controls) together with a decrease in concentration of immunoregulatory TGF-β1 (p<0.05) and elevated IL-10 (p<0.01) as compared to other groups. However, only IL-10 correlated with SLEDAI score (r=0.57) and negatively with levels of C4 (r=-0.59), probably as a compensatory mechanism related to immune activation. Conclusions: Our data suggest, that SLE associated lymphopenia affects primarily Treg and Th1, but not Th17 fraction, resulting in imbalance between regulatory and effector CD4+ subsets. This may lead to relative deficiency in suppressive function of Treg (as evidenced by decrease in TGF-β1), and consequently to the increased proinflammatory response during active phase of the disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3602